The Influence of Acquisition Experience and Performance on Acquisition Behavior: Evidence From the U.S. Commercial Banking Industry - Haleblian, Jerayr (John); Kim, Ji-yub (Jay); Rajagopalan, Nandini (Academy of Management Journal, 2006)
We draw upon theories of organizational learning to examine acquisition likelihood in a sample of banking industry acquisitions from 1988 through 2001. Although research on organizational learning suggests that routines arising both from experience and from performance feedback guide organizational learning, the combined effect of these two sources of learning has rarely been examined. Findings are consistent with our theoretical predictions: (1) prior acquisition experience, (2) recent acquisition performance, and (3) the interaction between acquisition experience and recent acquisition performance are all positively related to the likelihood of subsequent acquisition.